Drifting into debt? : exploring household over-indebtedness amongst salaried microborrowers in Bangladesh : a case study of Kailakuri Health Care Project : a thesis presented in partial fulfillment of the requirements for the degree of Masters of International Development, Massey University, Manuwatu, New Zealand - Vickers, Nadine (Massey University, 2017)
Salaried microborrowers in Bangladesh take loans for a variety of reasons but they can fall into repayment difficulties, leading to further loan-taking and potentially household overindebtedness. This thesis uses a case study of Kailakuri Health Care Project staff to explore over-indebtedness amongst salaried microborrowers. Data was gathered from two participantgroups, namely twenty four KHCP staff and eleven microfinance lenders. Four focus groups were held. Seven staff participated in a set of household interviews and financial diaries, which tracked their income, expenditure, savings and borrowing behaviour over a one-month period. The thesis explores local meanings of over-indebtedness and compares these to academic definitions. It compares the lending terms and conditions of microfinance lenders including moneylenders, banks, credit unions, NGOs and others with outstanding loans to research participants. It also examines how borrowers perceive the advantage and disadvantages of different lenders and the strategies they use to manage multiple repayments. Finally it considers how borrowers’ decision-making influences their risk of household over-indebtedness, as well as the effect of their income, expenditure, savings and borrowing-related behaviour. The research findings show that in contrast to the literature, which provides a mainly financial analysis, research participants focused on social symptoms of over-indebtedness such as the stigma attached to lender visits, deceitful behaviour by borrowers and debt-related stress. What is also illuminated is that borrowers weigh up a number of factors aside from interest rates when deciding on which lender to approach and they tend to prioritise NGO loan repayment because of the pressure on timely installments. This can lead borrowers to fall behind on other repayments to moneylenders, banks and credit unions, leading to an increased risk of overindebtedness. Many borrowers struggle with over-indebtedness because of insufficient income, social aspirations, cultural expectations and a number of other factors. However, microfinance lenders are unlikely to reduce interest rates and fees due to financial sustainability concerns. This thesis concludes that it is crucial to look outside the lender and borrower bubble and to consider the external pressures which are creating the demand for so much credit. The Bangladeshi government and international NGO community have an important role to play.
Keywords: Debt; Loans, Personal; Households; Economic aspects; Bangladesh; Research Subject Categories::SOCIAL SCIENCES::Social sciences; Microfinance